Interval Estimation for Quantile on Two Parameters Exponential Distribution Under Multiple Type-II Censoring on Complex Case with Bootstrap Percentile - Akhmad Fauzy (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
In this article, two methods are proposed to give the interval estimation for quantile on two parameters exponential distribution under multiply type II censoring. The interval estimation for quantile can be constructed the estimated parameters. Those researchers have use approximate maximum likelihood estimator to construct interval estimation for two parameters exponential distribution under multiply type II censoring. All of these method need an assumption that sample is exponentially distributed. We will use another method, known as the bootstrap percentile. This method gives shorter interval than the traditional method and this method does not need an assumption that the sample is distributed exponentially.